An evaluation of emergency field side care following implementation of the BokSmart program for rugby in South Africa - Green, Lidia (Division of Emergency Medicine, 2024)
Introduction Despite the varied health and social benefits of participating in sports, catastrophic injuries associated with rugby such as those of the spinal cord, brain, and cardiovascular system are rare but can be permanently debilitating or even fatal. To improve injury prevention and surveillance of catastrophic injuries the Chris Burger Petro Jackson Player Fund and South African Rugby Union implemented the BokSmart programme in 2011. The aim of this study is to assess and compare how emergency field side care was affected. Methods This observational and descriptive study collected data from the entire Chris Burger Petro Jackson Player Fund catastrophic injury database (n=147) between 2008 and 2019. The study was divided into three parts to describe and analyse: i) the epidemiology of catastrophic injuries in rugby over time, ii) immediate post-injury management and association with player outcomes, and iii) emergency care personnel levels and association with immediate post- injury management. Comparisons were made throughout between pre- and post- implementation of the BokSmart programme. Results There was a significant decrease in the distribution of catastrophic injuries between pre- and post-implementation of the BokSmart programme. Similarly, there was a significant decrease in the mean number of acute spinal cord injuries per year in the post-implementation period. The incidence of injuries occurring during high-impact scrums also substantially decreased. Post-implementation there was an increase in the proportion of incidents where first on-field medical support were registered medical care professionals. Injured players were also more likely to receive care that adhered to the BokSmart guidelines post-implementation; however, this ultimately made no difference in the outcome of acute spinal cord injuries and saw a decrease in the use of external resources like Spineline. Conclusion There has been a marked decrease in the mean number of catastrophic injuries per year following the implementation of the BokSmart programme, especially the proportion of acute spinal cord injuries following scrum law changes. This indicates that the BokSmart programme had a positive effect on emergency field-side care through decreasing catastrophic injuries from scrums, increasing the proportion of registered medical care professionals providing field-side care, and improved adherence to the BokSmart serious injury protocols. However, despite improved adherence, outcomes from acute spinal cord injuries have not improved. As there is little to no impact on the outcomes of spinal cord injuries due to the nature of the injury, a shift in focus towards prevention of catastrophic injuries and corresponding law changes should occur. The implementation of the BokSmart programme has shown to be effective through its educational programmes, injury surveillance, management, and reporting guidelines, to not only improve and optimise emergency field-side care, but also to reduce the incidence of catastrophic injuries across all levels of play in rugby.